2010
DOI: 10.1007/s10470-010-9483-7
|View full text |Cite
|
Sign up to set email alerts
|

A universal low-noise analog receiver baseband in 65-nm CMOS

Abstract: In this paper, a novel universal receiver baseband approach is introduced. The chain includes a postmixer noise shaping blocker pre-filter, a programmable-gain post mixer amplifier (PMA) with blocker suppression, a differential ramp-based novel linear-in-dB variable gain amplifier and a Sallen-Key output buffer. The 1.2-V chain is implemented in a 65-nm CMOS process, occupying a die area of 0.45 mm 2 . The total power consumption of the baseband chain is 11.5 mW. The device can be tuned across a bandwidth of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…By finding equivalent impeda GIC, it can be shown that two impe At node A, the impedance ZA is grounded, while the impedance at n when node A is grounded, so it is ca FDNR [2]. The AFFDNR works as PMA for instrumentation topology as…”
Section: Affdnr Based Feedback Netwmentioning
confidence: 99%
“…By finding equivalent impeda GIC, it can be shown that two impe At node A, the impedance ZA is grounded, while the impedance at n when node A is grounded, so it is ca FDNR [2]. The AFFDNR works as PMA for instrumentation topology as…”
Section: Affdnr Based Feedback Netwmentioning
confidence: 99%